2020
DOI: 10.1016/j.molcel.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The Alazami Syndrome-Associated Protein LARP7 Guides U6 Small Nuclear RNA Modification and Contributes to Splicing Robustness

Abstract: Highlights d LARP7 interacts simultaneously with the U6 snRNA and U6specific C/D box snoRNAs d Depletion of LARP7 results in reduced 2 0 -O-methylation of the U6 snRNA d Changes in alternative splicing are observed in the absence of LARP7 d A LARP7 mutation causes splicing alterations in Alazami syndrome patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 71 publications
5
46
0
Order By: Relevance
“…Although, loss of function mutation in LARP7 should cause uncontrolled growth, in contradiction, a restricted growth pattern has been observed (Alazami et al, 2012). Recently, alterations in splicing fidelity in LARP7 gene were suggested to play a role in the etiology of ALAZS (Hasler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although, loss of function mutation in LARP7 should cause uncontrolled growth, in contradiction, a restricted growth pattern has been observed (Alazami et al, 2012). Recently, alterations in splicing fidelity in LARP7 gene were suggested to play a role in the etiology of ALAZS (Hasler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…LARP7 family members likewise bind the 3′end of Pol III transcripts. However, they have apparently developed specificity for a subset of Pol III RNA targets [ 32 , 33 , 34 ], and facilitate specific functions, such as the stabilization of 7SKRNA or the 2′O methylation of the spliceosomal U6 small nuclear ribonucleic acid (snRNA) [ 35 , 36 , 37 , 38 , 39 ]…”
Section: Introductionmentioning
confidence: 99%
“…
Elegant studies by Hasler et al (2020) and Wang et al (2020) uncover a novel role of LARP7 in facilitating the 2 0 -O-methylation of the spliceosomal U6 snRNA, which is functionally required for fidelity of pre-mRNA splicing and development of male germ cells.
…”
mentioning
confidence: 99%
“…Among them, members of a large family of RNA-binding proteins (RBPs) that interact with target RNAs via the dedicated RNA-binding domains can affect all steps of gene expression. In a recent issue of Molecular Cell, the two studies by Meister, Fischer, and Liu laboratories reported an exemplary case of the RBP-driven control that could go awry (Hasler et al, 2020;Wang et al, 2020). The authors focused on La-related protein 7 (LARP7), of which reduced levels and loss-of-function gene mutations have been linked to cancer and Alazami syndrome, a severe developmental disorder.…”
mentioning
confidence: 99%